Loessial soils influenced by Pleistocene shell deposits of the Pascua Formation, northeastern Buenos Aires province, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In the littoral area of Buenos Aires province two carbonate Quaternary lithostratigraphic units linked to marine transgressions are found. In the most recent unit (Las Escobas Formation, Holocene) lithogenic calcareous soils (Calciudolls and Rendolls) are developed, which have been studied in their taxonomic, mineralogical and micromorphologic aspects (Vargas Gil et al., 1972; Sánchez, 1976; Imbellone, 1996; Imbellone and Giménez, 1997; 1998). Conversely, little information on the soils associated to the oldest unit (Pascua Formation, middle to upper Pleistocene) is available. This unit is interbedded in the upper part of the loessial sediments of the Pampiano Formation, consisting of sandy sediments with high amounts of mollusk shells strongly cemented with calcium carbonate forming a coquina (Fidalgo et al., 1973). These deposits are overlain by sediments of the Pampiano Formation, over 2 m in thickness, where Mollisols and Vertisols have been affected by calcification, vertisolization and clay illuviation processes. The objectives of this article are: a) to analyze the properties of the soils developed in loessic sediments overlying the Pascua Formation, and b) to estimate the influence of the carbonate deposits of this formation in the soil genesis. Five pedons (four Mollisols and one Vertisol) located in the municipalities of La Plata, Magdalena and Punta Indio (Buenos Aires province, Argentina, Fig. 1) were studied. The soils have developed in an upland plain adjacent to coastal plains. The climate is temperate-humid, with a mean annual rainfall of 1040 mm, fairly well distributed; mean annual temperature is 16.2 oC (La Plata city, latitude 34o 55’ S, longitude 57o 56’ W, altitude 15 m a.s.l.). The monthly mean water balance shows a small deficit (7 mm) in summer and a substantial surplus (240 mm) between autumn and spring. The soil moisture regime is udic and the soil temperature regime is thermic. According to the classification of Thornthwaite (1948) the climate of the area is B1 B´2 r a´. Native vegetation is dominated by grasslands, largely modified by agriculture and grazing. The studied soils are polygenetic due to the geomorphologic evolution of the area. The sedimentary deposits include: a) transgressive deposits of the Querandinense ingression (humid climate) at the base; b) Postquerandinense eolian deposits (dry climate) and c) Postplatense deposits (dry climate) in the upper part. Pedons 2, 3, 4 and 5 have developed in loessial sediments. Unlike other carbonatic soils of the coastal plains, they are practically devoid of primary carbonate. On the other hand, Pedon 1 would have developed in a mixed deposit: an upper soil including shell fragments (Holocene), overlying a calcrete formed in a Pleistocene loessial deposit (Fig. 2, Table 1).The presence of pedogenic carbonate is revealed by macromorphological features such as pseudomycelia, soft powdery masses, some concretions and diffuse accumulations in root pores in the upper part of the solum, whereas the horizons overlying the rock contain lithogenic calcareous pebbles and shell fragments, as well as some pedogenic carbonates (soft powdery masses). Pedons 2, 3, 4 and 5 have a similar distribution of CaCO3 equivalent in depth. The carbonate is absent or has
Keywords: Calcareous Soils, Pedogenic Calcium Carbonate, Calcrete, Littoral Buenos Aires Province.